Implementasi Supervisi Akademik Kepala Sekolah Dalam Meningkatkan Kompetensi Pedagogik Guru di SMPIT Mutiara Ilmu Bangkalan - Hanaris, Fitria (Jurnal Administrasi Pendidikan Islam, 2025)
This study aims to analyze the implementation of academic supervision by the school principal in enhancing teachers' pedagogical competence at SMPIT Mutiara Ilmu Bangkalan. The research is driven by the phenomenon of "supervision anxiety" among teachers and the principal's time constraints. A qualitative descriptive approach was utilized. Data were gathered through in-depth interviews, classroom observations, and documentation, then analyzed using the Miles and Huberman model. The findings indicate that supervision is implemented through three systematic stages: collaborative planning, humanistic-Islamic observation, and digital-based evaluation. To mitigate psychological barriers, the principal internalizes Islamic values such as ukhuwah (brotherhood). The integration of Information Technology (IT) in the supervision process significantly enhances time efficiency. This holistic model effectively improves teachers' pedagogical skills, particularly in lesson planning and the integration of Islamic values across the curriculum.